2023
DOI: 10.1007/s40684-023-00527-2
|View full text |Cite
|
Sign up to set email alerts
|

Storage of High-Strength Steel Flux-Cored Welding Wires in Urbanized Areas

Abstract: The condition of the consumables is a key factor determining the waste reduction in the welding processes and the quality of the welded joint. The paper presents the results of tests of four types of flux-cored wires dedicated for welding high-strength steels, stored for 1 month and 6 months in Poland in two urbanized areas: in a large seaside city (Gdańsk) and in Warsaw, located in the center of the country. The wires were subjected to macroscopic and microscopic (stereoscopic, SEM) observations, EDS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The average hydrogen levels were 38.6 ml/100g and 84.5 ml/100g for air and water, respectively, and these are consistent with literature data for welding with rutile covered electrodes [33,34].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The average hydrogen levels were 38.6 ml/100g and 84.5 ml/100g for air and water, respectively, and these are consistent with literature data for welding with rutile covered electrodes [33,34].…”
Section: Resultssupporting
confidence: 90%
“…According to the results of the analysis carried out and industrial experience, it can be concluded that the environment and steel grade significantly affect morphology and properties of metal subjected to rapid thermal cycle [34]. Arc strikes are a highly disregarded welding imperfection among the unacceptable ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, with a rise in CE value and mechanical strength for E410 and above; satisfactory weldability and to achieve high strength welding is a challenging issue; owing to which not much usage of E410 and above exists in public infrastructure. Few studies have highlighted these problems of weldability resulting from different causes (Wolski et al, 2023;Swierczy nska et al, 2024). Therefore, research on these aspects is essential as remarked earlier by Samanta et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…The flux-cored arc welding process is increasingly used in many industries, including construction, automobile production, agriculture, mining, etc. [27][28][29][30][31]. The growing demand for flux-cored wires is justified by the advantages of welding methods.…”
Section: Introductionmentioning
confidence: 99%